Uncovering Indonesia’s Sectoral Interdependencies in Global Value Chains: A Hypothetical Extraction Approach - Potenza, Maura Bintang; Farisi , M. Al; Suwarno, Alicia Ramadhani Putri; Kartiasih, Fitri; Yuliana, Rita (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study extends the multiregional input-output approach by longitudinally decomposing Indonesia’s sectoral and intercountry linkages with major ASEAN FTA partners, providing a dynamic perspective on Indonesia’s evolving role in global value chains over a 15-year period. Research Objectives: This study aims to assess the economic interdependence between Indonesia and five ASEAN FTA partners, focusing on sectoral contributions and spatial trade dynamics. Research Methods: This study applies the Hypothetical Extraction Method (HEM) to panel data from the World Input-Output Database (WIOD) spanning 2000 to 2014 to measure sectoral and spatial linkages. Empirical Results: This study shows that the construction sector has the strongest backward linkages, while mining and manufacturing dominate forward linkages. Mining’s forward linkages tripled between 2000 and 2014, indicating rising global dependence on Indonesian commodities. Intercountry backward linkages declined from 25.46% to 19.95%, suggesting increased domestic input substitution, whereas intercountry forward linkages rose, reinforcing Indonesia’s role as a global supplier. Additionally, China has overtaken Japan and Australia as Indonesia’s main trading partner. Implications: The findings highlight the need to strengthen key sectors and pursue selective import substitution to boost Indonesia’s competitiveness and resilience. JEL Classification: F14, F15, C67